PENGARUH PEMBIAYAAN TERHADAP PENDAPATAN ANGGOTA PADA KOPERASI JASA KEUANGAN SYARIAH BMT ARTHA JAYA (STUDI KASUS KJKS BMT ARTHA JAYA KEC. BABELAN KAB. BEKASI) - Agus Purwo Wicaksono; Andi M. Rudhan; Iwan Darmawansyah (Journal of Innovation Research and Knowledge, 2023)
Small and medium micro enterprises or commonly called SMEs is wrong one supporter of the economy that must be developed. Recently economic growth is directed at developing industrial sectors, and small and medium-sized micro enterprises (SMEs) really contribute substantially to economic growth. In the development of SMEs in the form of cooperative institutions that serve the community in general, such as sharia financial services cooperative, this cooperative in serving the community to meet various obstacles that are still faced and the main obstacle is the cost / capital for small businesses. In reality there are some possible sources of funding for small businesses, but are delayed by lack of information and again small industries (SMEs) do not have adequate administrative facilities which is one of the requirements to obtain credit. To solve the problem, then comes BMT. BMT is a financial institution in charge of distributing financing / credit for micro, small and medium enterprises with credit procedures that are faster, safer, efficient and easy. The purpose of the cooperative form such as BMT is to prevent loan sharks and the practice of bonds. In providing financing BMT cooperatives require certain guarantees as a condition of members in obtaining loans, which reduces the risk of credit loss. In providing BMT cooperative financing more selective to its members. Capital established the cooperative BMT from the board and permanent members BMT who provide basic fee as the initial capital of the cooperative, and then other permanent members who join in the business in the Cooperative BMT, which is also operated there are daily administrators and regulatory bodies.